New Ways of Detecting ADRs in Neonates and Children - Jimenez, Ricardo; Smith, Anne; Carleton, Bruce (Current Pharmaceutical Design, 2015)
Severe adverse drug reactions (ADRs) cause 5-7% of all hospital admissions, an estimated 2,000,000 severe reactions, and over 100,000 deaths each year in the USA. A recent systematic review indicated that the overall incidence of ADRs was 11% in hospitalized children and 1% in outpatients. Detecting ADRs in neonates and children is challenging, particularly because there are fewer clinical trials involving children than adults and drug use in children is common without a labeled indication. Ontogeny and significant physiological changes related to age have an impact on metabolic drug clearance and pharmacodynamics in children compared to adults, as well as on drug action. A variety of strategies have been developed for the identification and further evaluation of ADRs, starting from case reports and advancing into more structured methodologies, such as active surveillance, for accumulating the necessary information. While each approach has merit, a comprehensive surveillance approach with different methods is required to monitor drug safety in the post-market period. Among the methods that have shown value in neonates and children are anecdotal reporting, voluntary organized reporting, prescription event monitoring, pharmacoepidemiology using administrative databases, and active surveillance. There is an urgent need to improve the evaluation of paediatric drug safety in the pre- and post-market phases of drug evaluation in order to better predict in whom serious harm may occur and better ensure the safe use of drugs for neonates and children.
Keywords: children